Visual performance of elite hockey players - A longitudinal analysis - Oertzen-Hagemann, V.; Jendrusch, G.; Platen, P. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: Visual performance in sports, especially sports and racket games, undisputably influences sporting performance. In Germany, however, eyesight tests for the analysis of visual performance and the detection of ametropia/defective vision are only integrated in the routine health check or performance diagnostics in few sports. The aim of this study was to analyze, if regular visual testing of competitive sportsmen is effective in the sense of visual performance optimization and which further consequences will occur. Methods: Visual test data from the male (n=110, mean age 20.4+/-2.7 years) and female (n=143, mean age 20.7+/-3.3 years) national field hockey teams were evaluated, which were collected over a period of seven years (2006-2013) in annual health and performance diagnostics. The players (female: n=25; male: n=27) that were included in the longitudinal analysis took part in the eyesight tests at least four times during the testing period. The rate of ametropia, the compliance (related to the medical recommendation) and the group-related development of monocular visual acuity (VA) were analyzed. Results: For the complete sample (n=253) the median of visual acuity was VA=1.60 for both eyes (P25=1.27, P75=2.00). It is notable that during the first eyesight test 24 % of the athletes were classified as "ametropic" (i.e. in need of correction). In the group-related longitudinal section VA of the men increased significantly from the first test (right eye (R.E.)=1.61, P25=1.06, P75=1.85; left eye (L.E.)=1.59, P25=1.22, P75=1.95) to the second test (R.E.=2.00, P25=1.60, P75=2.25; 2p=0.001 / L.E.=2.00, P25=1.60, P75=2.00; 2p=0.009) and then stayed on a very high level (VA=2.00). VA of the women showed no significant difference between the four tests (first test: R.E.=1.60, P25=1.26, P75=1.70 / L.E.=1.60, P25=1.26, P75=1.80; fourth test: R.E.=1.80, P25=1.41, P75=2.00 / L.E.=1.60, P25=1.60, P75=2.00; p=0.069) - related to the men on an overall low level. The reason is the higher rate of ametropia - which developed during the testing period - in the women group (36 %) compared to the men (11 %). VA of the men improved significantly during the multiannual testing compared to the median of the complete sample (p<0.01). The compliance of the men (with 50 %) is better than those of the women, from which only 45 % followed the medical advices. Conclusion: The results show the necessity of regular visual testing concerning sporting performance and the prevention of injuries and accidents. Ametropia often develops in the ages in which competitive sports are practiced and may have negative influences on sports performance. The partly bad compliance confirms that the trainers and athletes need to strengthen their awareness of the problems concerning eyesight for the sake of safety and performance.